Population Size and Habitat Patterns of Indo-Pacific Humpback Dolphins (Sousa chinensis) off Donsak, Surat Thani, Thailand - Suwat Jutapruet" (Science Faculty of Chiang Mai University, 2019)
This study investigated the population size and distribution pattern of the Indo-Pacific humpback dolphin (Soasa chinesis) off Donsak, Surat Thani, Thailand. The field surveys were conducted along the coastline of the mainland and the offshore area of the Angthong Marine National Park. The population size was estimated by applying a mark-recapture model to the individual photo-identification records collected from field surveys. In total, 142 individuals were photo-identified using dorsal fin characteristics. The population size was estimated to consist of 160 individuals with a range of 152 – 178 at a 95% CI. Spatial (GPS data) and environmental information were recorded for distribution and habitat analysis. The most frequent encounters with humpback dolphins occurred, in decreasing order of magnitude, at Somserm Ferry, Raja Ferry, Som Island, Nok Ta Pao Island and Taled Bay. The present study showed that the humpback dolphins off Donsak were frequently found near the coast in close proximity to man-made structures, sea grass areas and mudflat habitats. Our study revealed that a distinct humpback dolphin habitat occurred at a specific off-shore distance, water depth and water transparency. Results of this study improves the better understanding of the humpback dolphin’s ecology and offers informed baselines essential for meaningful marine-mammal protection and management policies in the Gulf of Thailand.